Performance and Age of Companies Listed on the Bombay Stock Exchange - Kar, Brajaballav; Jena, Manoj Kumar (Indian Journal of Finance, 2019)
Is there any relation between age and financial performance of the organizations? One school of thought believes that with age, the organizations’ learning capability matures, and the processes improve to deliver the best financial performance. The other school argues that with advancing age and rigidity of processes, the decision making ability and response to the market reduces. Thus, these two schools of thought present diametrically opposite ideas related to performance of firms with age. This research took panel data for 5 years (2012-16) on various performance parameters such as income, asset, compounded annual growth, earnings before interest, tax, depreciation and amortization (EBITDA), net profit margin, return on net worth, and return on capital employed for 3719 companies listed on the Bombay Stock Exchange. The companies were categorized into 12 sectors. Each financial parameter was compared with age of the companies across sectors to find any significant correlation. The study found that the (a) age and performance parameters were not normally distributed, (b) most of the companies showed negative financial performance on chosen parameters across sectors, (c) asset, income, and compound annual growth rate had weak, negative, but significant correlation with age, (d) earnings before interest, tax, depreciation and amortization margin had a weak but positive correlation with age. Thus, the older companies indicated better operational efficiencies compared to the market competitiveness. The study covered a period where the Sensex was consistently rising. A fine grained and detailed understanding may be obtained with similar studies for specific sectors and other time periods.